Safety-guaranteed and task-consistent human-robot interaction using high-order time-varying control barrier functions and quadratic programs - Shi, Kaige (2024)
Close human-robot interaction enables the combination of complementary abilities of humans and robots, thereby promoting efficient manufacturing. Human safety is an important aspect of human-robot interaction. To this end, the robot executes an evasive motion for collision avoidance when the human approaches. However, the evasive motion may be inconsistent with the robot's task resulting in unresumable task failure. In this letter, a control framework is proposed to achieve guaranteed human safety and hierarchical task consistency. First, the high-order time-varying control barrier function (HO-TV-CBF) is proposed to keep a safe distance between human and robot, thereby guaranteeing human safety. Next, to achieve hierarchical task consistency, a hard constraint and a soft constraint are defined systematically. The hard constraint ensures primary task consistency that keeps the task resumable, while the soft constraint together with the hard constraint ensures full task consistency. Finally, two quadratic programs (QPs) are employed to coordinate different control objectives, i.e., human safety and primary task consistency are always guaranteed while full task consistency is ensured whenever possible. Experiments are conducted to validate the proposed control framework with comparisons to existing methods.